Estudo térmico e oxidativo em diferentes matrizes de biodiesel com adição de antioxidantes - Oliveira, Rodrigo Matiello (2012)
The action of an antioxidant is related to the chemical composition of the biodiesel to which it is added. Considering the current importance of the biodiesel industry, their need for antioxidants, the crop yield potential of jatropha (Jatropha curcas L.) and wild radish (Raphanus sativus L.) it ´s necessary to study the efficiency of antioxidants to increase the shelf life of biodiesel, avoid waste and provide increased profitability. The objective of this study was to test antioxidants Butylhydroxytoluene, Propyl Gallate and Pyrogallic Acid in a concentration of 1000ppm (w/w) in biodiesel of jatropha, raphanus and soybean after aging treatment, using thermogravimetry analysis. The biodiesel were obtained by transesterification using methylic route, obtaining approximate yield of 90% and were characterized by physico-chemical and analytical techniques such as thermogravimetry analysis and infrared spectroscopy. The aging through thermal and oxidative degradation was performed under synthetic air flow and temperature of up to 150°C for 24 hours. Aliquots were collected for thermogravimetry analysis and infrared spectroscopy in the treatment times 0, 6, 12 and 24 hours. The thermogravimetry analysis was obtained from ambient temperature to 550°C at a heating rate of 10°C/min. The atmosphere used was nitrogen with flow 100mL/min and disposable in uncovered aluminum crucibles. Under the analysis of data of thermogravimetry it was possible to estimate the thermal and oxidative stability of biodiesel with and without antioxidants. Loss steps mass were observed and assigned to volatilization and/or degradation of biodiesel, change in the profile thermogravimetry, increased number of steps of lost mass over the time of aging treatment, indicating the formation of compounds of autoxidation biodiesel, which is being observed by changing the temperature Onset. It was estimated for each biodiesel, an order of efficiency of antioxidants, mainly based on analysis of the thermogravimetric curves and parameters such as solubility and the market price, finding the following orders: jatropha biodiesel - Butylhydroxytoluene < Propyl Gallate < Pyrogallic Acid; raphanusbiodiesel - Butylhydroxytoluene < Propyl Gallate < Pyrogallic Acid; soybean biodiesel - Propyl Gallate < Pyrogallic Acid < Butylhydroxytoluene